2018
DOI: 10.1080/00324728.2017.1404624
|View full text |Cite
|
Sign up to set email alerts
|

The changing relationship between unemployment and total fertility

Abstract: The aim of this paper is to investigate whether there has been a fundamental change in the relationship between economic conditions and fertility. We use panel data methods to study the short-term changes in total fertility and the unemployment rate in a range of Organisation for Economic Co-operation and Development (OECD) countries from 1957 to 2014. We find that although fertility was counter-cyclical before 1970, with good economic times being associated with lower fertility, since then it has become pro-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…The timing of the fertility-rate contraction suggests a link with the global economic and financial crisis that plagued most advanced economies in 2008 and some years thereafter. Research has shown that fertility rates in advanced economies are pro-cyclical, so they tend to rise with economic growth and decline with stagnation or recession (Sobotka et al 2011 ; Comolli 2017 ; Örsal and Goldstein 2018 ). The cyclicality of fertility rates in the Nordic region has not been systematically studied in comparative terms prior to this study, neither across the five Nordic countries nor across the two economic crises that hit the region during the last decades.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The timing of the fertility-rate contraction suggests a link with the global economic and financial crisis that plagued most advanced economies in 2008 and some years thereafter. Research has shown that fertility rates in advanced economies are pro-cyclical, so they tend to rise with economic growth and decline with stagnation or recession (Sobotka et al 2011 ; Comolli 2017 ; Örsal and Goldstein 2018 ). The cyclicality of fertility rates in the Nordic region has not been systematically studied in comparative terms prior to this study, neither across the five Nordic countries nor across the two economic crises that hit the region during the last decades.…”
Section: Discussionmentioning
confidence: 99%
“…Based on aggregate data, the cyclicality of fertility rates in relation to business cycles has been studied quite extensively in recent years. Empirical research generally shows that TFRs tend to decline during economic downturns in response to increasing unemployment and labor-market insecurity, dropping prices in the housing market, declines in consumer confidence, and increased financial uncertainty (Schneider 2015 ; Comolli 2017 ; Örsal and Goldstein 2018 ) but that extensive welfare-state support may alleviate much negative impacts of economic depressions on fertility (Myrdal 1945 ; Sobotka et al 2011 ). In general, most studies find that fertility declines are temporary and constitute mainly a postponement of births among younger women (for a review see Sobotka et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of adolescent reproductive health services, harmful traditional practices, lack of privacy and inconvenient service hour were reasons for not utilizing the service (10). Relationship between unemployment and total fertility showed that, although fertility was counter-cyclical before 1970, with good economic times being associated with lower fertility, since then it has become pro-cyclical, with good economic times being associated with higher fertility (11). Lack of proper access to health services has been associated with serious ill-health ranging from reproductive tract infection, urinary tract infection, etc.…”
Section: Discussionmentioning
confidence: 99%
“…These occasions bankrupted several organizations, little to extensive. In the two cases, use was the name of the diversion and bank resources and liabilities were horribly confounded (Karaman , et al,2018). Cash was shabby and when the gathering finished, financing costs moved higher and banks imploded.…”
Section: Operational Riskmentioning
confidence: 99%